An ex ante analysis of the impact and cost-effectiveness of biofortified high-provitamin A and high-iron banana in Uganda - Fiedler, John L.; Kilkuwe, Enoch M.; Birol, Ekin (International Food Policy Research Institute, 2013)
Using the Ugandan National Household Survey of 2005/06, we analyzed the production and consumption patterns of highland cooking banana (nakinyika) and sweet banana (sukalindizi). Informed by the empirical findings, we developed geographically differentiated adoption, production, consumption, and diffusion patterns for several types of HPVAHIB. Based on households’ reported quantities of each type of banana currently consumed, we estimated the number of people consuming each banana and the quantities they consume, and then simulated the additional intakes of vitamin A and iron and estimated the number of disability-adjusted life years (DALYs) saved attributable to each.